NOMOPHOBIA, SLEEP DEPRIVATION AND LEISURE ACTIVITIES IN ADOLESCENTS AND YOUNG ADULTS - Zeb, Ayesha; Bibi, Humaira; Khan, Mussarat Jabeen; Awan, Sumaira Naz (Pakistan Journal of Physiology, 2022)
Background: Nomophobia is mobile phone addiction, characterized by an intense and irrational fear of being without a mobile phone, which affects the sleep and leisure activities of youth. The study examined the relationship between nomophobia, sleep deprivation, and leisure activities. It also measured the mediating role of nomophobia between sleep deprivation and leisure activities and find out demographic differences (age, gender, education, socioeconomic status) on nomophobia, sleep deprivation, and leisure activities. Methods: Conveniently selected sample of 500 adolescents and young adults from Khyber Pakhtunkhwa, after informed consent, was measured on Nomophobia Questionnaire, Athens Insomnia Scale, and Pittsburg Enjoyable Activities Scale. The data were collected from March to August 2019. The sample was further divided based on age (adolescents 250) (young adults 250). Results: Nomophobia has a significant positive correlation with sleep deprivation and has a significant negative correlation with leisure activities. Nomophobia significantly mediated between sleep deprivation and leisure activities. Significant differences of age, socio-economic status, and education on nomophobia, sleep deprivation, and leisure activities were found. Furthermore, significant gender differences were found on nomophobia and leisure activities, while non-significant gender differences were concluded on sleep deprivation. Conclusion: Nomophobia and sleep deprivation are greater in adolescents who belong to lower social class, while involvement in leisure activities is higher in young adults who belong to upper social class. Females have a higher level of nomophobia and involve less in leisure activities than males. Pak J Physiol 2022;18(3):30?4